Optimal child-related transfers with endogenous fertility - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, 2015)
To compare the systems of child benefits and of family tax deductions, we create a model with endogenous fertility and a basic income, also financed from proportional wage taxes. The deduction's efficiency is presumably lower than the benefit's and may even be lower than that of pure basic income.
Keywords: J13; 330; progressive income tax; child benefits; family tax deductions; endogenous fertility